2019
DOI: 10.3847/2041-8213/ab1f6c
|View full text |Cite
|
Sign up to set email alerts
|

The Physical Nature of Spiral Wave Patterns in Sunspots

Abstract: Recently, spiral wave patterns (SWPs) have been detected in 3 minute oscillations of sunspot umbrae, but the nature of this phenomenon has remained elusive. We present a theoretical model that interprets the observed SWPs as the superposition of two different azimuthal modes of slow magnetoacoustic waves driven below the surface in an untwisted and non-rotating magnetic cylinder. We apply this model to SWPs of the line-of-sight (LOS) velocity in a pore observed by the Fast Imaging Solar Spectrograph installed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 38 publications
5
30
0
Order By: Relevance
“…Recent observations (Chae et al 2017;Cho et al 2019;Kang et al 2019) rather support the notion that the sources of excitation are located below the atmosphere, as has commonly been modeled by the piston motion at the bottom of the atmosphere in previous theoretical studies (e.g., Fleck & Schmitz 1991;Kalkofen et al 1994;Sutmann & Ulmschneider 1995). These studies found that regardless of the specific form of the piston driving, the oscillations with a frequency close to the cutoff prevail in high altitudes of the atmosphere.…”
Section: Introductionmentioning
confidence: 73%
“…Recent observations (Chae et al 2017;Cho et al 2019;Kang et al 2019) rather support the notion that the sources of excitation are located below the atmosphere, as has commonly been modeled by the piston motion at the bottom of the atmosphere in previous theoretical studies (e.g., Fleck & Schmitz 1991;Kalkofen et al 1994;Sutmann & Ulmschneider 1995). These studies found that regardless of the specific form of the piston driving, the oscillations with a frequency close to the cutoff prevail in high altitudes of the atmosphere.…”
Section: Introductionmentioning
confidence: 73%
“…The same can be said for waves in chromospheres above sunspot umbrae. For instance, the long-known spiral wave patterns (SWPs) with periodicities of ∼ 3 mins (e.g., Su et al 2016, and references therein) were recently shown to be compatible with the superposition of slow body modes with m = 0 and m = 1 (m = 0 and m = 2) in the case of one-armed (two-armed) SWPs (Kang et al 2019). Likewise, clear signatures of slow kink body modes were identified in the temporally and spatially filtered H α image sequences acquired with ROSA mounted on the Dunn Solar Telescope (DST, Jess et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It has been assumed that the waveguides of running waves are twisted into local spiral structures [14]. A model for the appearance of spiral wavefronts was proposed in relation to their propagation in radial magnetic fields [15]. The authors concluded that rotating structures can occur in a superposition of non-zero- m azimuthal slow modes.…”
Section: Introductionmentioning
confidence: 99%